Study the Spectral Properties of the Molecule [Pentacene (C22H14)] by Using Semi-empirical Quantum Programs - Galsan T. Kamal; Abdul Hakim Sh. Mohammed; N. K. Hassan (Tikrit Journal of Pure Science)
The Study aims to determine the spectral properties of the molecule pentacene (C22H14) by using Semi-empirical quantum programs [Hyper Chem8.0, WinMopac7.21] by (MNDO–PM3) (Modified Neglect of Differential Overlap-Parameterization Model3). The study cover calculations of the space geometrical shape of pentacene molecule has been calculated by using  initial and final matrixes, including length, the angle between bonds, dihedral angles and the charge of each  atom in the pentacene molecules. Total energy, the electronic energy, zero point energy, energy gap, core-core repulsion, ionization energy, and dipole moment for molecule were calculate. Curved potential energy per molecule was drawn where it was adopted to change the length of the bonds (C1-C2),(C1=C4), and (C1-H23) in the pentacene molecule. As well, as have been obtained vibration frequencies of pentacene in (IR) region and electronic transition in (UV) region. The study’s results were in agreement with the previous research..